Effect of dietary carbadox or formic acid and fibre level on ileal and faecal nutrient digestibility and microbial metabolite concentrations in ileal digesta of the pig - Partanen, Kirsi; Jalava, Taina; Valaja, Jarmo; Perttilä, Sini; Siljander-Rasi, Hilkka; Lindeberg, Heli (Elsevier, 2001)
A digestibility trial was carried out on six castrates (39-83 kg body weight) in a 6 x 4 change-over design to investigate the effects of dietary carbadox (50 mg/kg feed) and formic acid (8 g/kg feed) supplementations on the apparent ileal and faecal digestibility of nutrients and fermentation characteristics in the ileal digesta of pigs fed medium- or high-fibre diets (neutral detergent fibre 189 and 219 g/kg dry matter, respectively). The pigs were fitted with T-cannulas according to the steered ileaocaecal valve technique. The true ileal digestibility of lysine supplied by soyabean meal was determined by the homoarginine method. Both carbadox and formic acid improved significantly the apparent ileal digestibility of several essential and nonessential amino acids in the high-fibre diet but not in the medium-fibre diet. Neither carbadox nor formic acid influenced the true ileal digestibility of lysine supplied by soyabean meal (P = 0.78). The additives decreased the ileal flow of purines (P = 0.01) and tended to decrease that of bacterial nitrogen (P = 0.07), which indicates that improved apparent ileal amino acid digestibilities were probably due to reduced bacterial protein synthesis in the ileal digesta. The additives increased the apparent ileal and faecal digestibilities of ether extract (P = 0.01), formic acid more than carbadox (P = 0.01). The apparent ileal digestibilities of crude protein and calcium were improved in the high-fibre diet (P = 0.01) but not in the medium-fibre diet (P = 0.87 and 0.80, respectively). The additives decreased the lactate (P = 0.02) and increased the acetate concentration (P = 0.01) in ileal digesta samples 6 h postprandial. The change in lactate concentration was greater for the formic acid than carbadox supplemented diets (P = 0.01). Propionate, n-butyrate and ammonia concentrations were not influenced significantly by dietary treatments. In conclusion, the positive effect of dietary carbadox or formic acid supplementation on the apparent ileal digestibility of protein and other nutrients depended on diet composition. The additives did not affect the true ileal digestibility in soyabean meal. The improved apparent ileal amino acid digestibilities were probably partly due to the reduced flow of bacterial nitrogen in the ileum, but this requires further investigation.
Keywords: Ko; sika; sulavuus; orgaaniset hapot; antibiootit; aminohapot; rehut; pigs; organic acids; antibiotics; digestibility; amino acids; pig; antibiotics; organic acids; fibre; digestibility; microbial metabolites